2021
DOI: 10.3390/nu13124440
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin in Metabolic Health and Disease

Abstract: In recent years, epidemiological studies have suggested that metabolic disorders are nutritionally dependent. A healthy diet that is rich in polyphenols may be beneficial in the treatment of metabolic diseases such as polycystic ovary syndrome, metabolic syndrome, non-alcoholic fatty liver disease, cardiovascular disease, and, in particular, atherosclerosis. Curcumin is a polyphenol found in turmeric and has been reported to have antioxidant, anti-inflammatory, hepatoprotective, anti-atherosclerotic, and antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…CLR has been reported to exhibit anti-oxidant, anti-inflammatory, hepatoprotective, anti-atherosclerotic, and anti-diabetic properties [ 11 ]. Curcumins are the characteristic components in CLR, which is also a phenylpropanoid derivative and a member of the diketone family.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CLR has been reported to exhibit anti-oxidant, anti-inflammatory, hepatoprotective, anti-atherosclerotic, and anti-diabetic properties [ 11 ]. Curcumins are the characteristic components in CLR, which is also a phenylpropanoid derivative and a member of the diketone family.…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin is a characteristic component of CLR and exhibits anti-infammatory, antioxidation, antitumor, and immunoregulatory properties. Moreover, it improves insulin resistance, obesity, and other FFA-related diseases [11,[28][29][30][31]. In this study, isoquercetin and rutin were also screened as representative compounds.…”
Section: Identifcation Of Prototypes and Metabolites Of Xrg-4 Inmentioning
confidence: 99%
“…Currently, curcumin is largely used for its multiplex biological activities, which include anti-inflammatory activity, antioxidant activity, stem cell modulation, regulation of mitochondrial homeostasis, and neurogenesis [ 50 ]. Consequently, curcumin could be useful in the treatment of a large range of diseases, including metabolic, inflammatory, and cardiovascular ones [ 51 ]. In recent decades, natural compounds—and curcumin in particular—have gained growing interest in both experimental and preclinical studies for their beneficial effects on the central nervous system (CNS) [ 52 ].…”
Section: Natural Compounds In the Therapy Of Gliomamentioning
confidence: 99%
“…It is challenging to dissolve, extract, and absorb curcumin, resulting in low bioavailability and limited clinical applications ( Esatbeyoglu et al, 2012 ; Kotha and Luthria, 2019 ). In recent years, numerous drug delivery systems using liposomes, nanoparticles, and microemulsion as carriers have been successfully developed, which significantly increased the solubility, stability, and safety of curcumin, and greatly improved its biological activity in treating or preventing diseases, showing great promise for clinical application ( Aggarwal and Sung, 2009 ; Mahmood et al, 2015 ; Abd El-Hack et al, 2021 ; Jabczyk et al, 2021 ; Feltrin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…( Zhou et al, 2011 ; Mandal et al, 2020 ; Fu et al, 2021 ). Numerous studies have revealed the beneficial role of curcumin in cancer, diabetes, metabolic diseases, autoimmune diseases, atherosclerosis, arthritis, pulmonary diseases, etc ( Aggarwal and Harikumar, 2009 ; Jabczyk et al, 2021 ; Mahjoob and Stochaj, 2021 ). Recently, researchers discovered that curcumin also has neuroprotective effects on various neurological diseases, including neuropsychiatric disorders, neurodegenerative diseases, traumatic brain injury, spinal cord injury, and epilepsy ( Dhir, 2018 ; Bhat et al, 2019 ; Yavarpour-Bali et al, 2019 ; Yuan et al, 2019 ; Farkhondeh et al, 2020 ; Nebrisi, 2021 ; Lamanna-Rama et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%